Strengthening Rural Extension Services to Facilitate Community towards Sustainable Development Goals in Three Districts in Indonesia - Amanah, Siti; Fatchiya, Anna (Jurnal Penyuluhan, 2018)
Rural areas in Indonesia vary in terms of socio-economics and cultural background, the landscape, physical climate, the resources, and the accessibility to extension services. Rural extension services play an important role in facilitating community development from on-farm to off farm activities. Rural extension systems have to address the increased demand for the services and to nd innovative approaches and strategies to facilitate community in the era of globalization. The paper aims to analyse the current status of rural extension systems in Indonesia, to analyse the role of stakeholders involved in extension systems, and to formulate plan and actions to strengthen rural extension systems. Assessment of rural extension systems was conducted by using a logical framework analysis models involving representatives from rural community groups and resource persons. Stakeholder dialogues and group discussions were conducted to gather information and to discuss the issues on rural extension. Data were analysed using stakeholders analysis to formulate strategy to strengthen rural extension systems. The results indicate that rural areas have shown changes in terms of socio-ecological aspects, land-uses, sources of income, and availability of resources. The changes are due to population increases that result in the need for more food, housing, education, jobs, and other public facilities. Community groups run small enterprise in rural areas for income generating activities. Engaging community and related stakeholders in the systems has positive effects for successful rural extension services. Stakeholder analysis showed that better collaborative extension services from service providers is needed to facilitate community. In terms of sustainable development goals, rural extension systems need the issues of food, health, water, gender, poverty and environment to be integrated into the services. Existing supports from local government, business sectors, civil society organizations, and universities are essentials to facilitate transformative changes in communities.